Salivary protein biomarkers associated with orthodontic tooth movement: A systematic review. (10th May 2019) - Allen, Riley K.; Edelmann, Alexander R.; Abdulmajeed, Aous; Bencharit, Sompop
Structured Abstract: Objective: Saliva can provide a non‐invasive approach to indicate changes in the oral and systemic conditions. Salivary proteomics allows the discovery of new protein biomarkers associated with certain conditions. The effectiveness and physiological effects of orthodontic tooth movement in theory can be measured using salivary protein biomarkers. Setting and Sample Population: This study applied a systematic review to analyse current literature to define and summarize salivary biomarkers associated with orthodontic tooth movement identified by mass spectrometry proteomics and other protein detection techniques. Materials and Methods: Peer‐reviewed articles published through the 15th of November 2018 via the PubMed, EMBASE, Web of Science and Dentistry & Oral Sciences databases were reviewed. Only studies analysing protein biomarkers in saliva samples collected from human subjects associated with orthodontic treatments were included. Results: Out of 482 articles, 7 studies were selected. Sample size ranged from 3 to 72 subjects. Minor variations of unstimulated whole saliva sample collection protocol were noted. Mass spectrometry proteomics and ELISA represented the majority of biomarker discovery and targeting, respectively. Twenty biomarkers were identified or chosen as target biomarkers. Conclusion: Salivary proteins may be used to indicate effectiveness of orthodontic treatment and orthognathic treatment as well as adverse treatment consequence, such as root resorption.